(untitled) (Global Journal of Human-Social Science, 2012)
In recent times the problem of environmental degradation of urban areas in Nigeria has reached an unprecedented proportion This phenomenon which is prevalent in both residential and industrial areas is caused by increased population growth unsustainable use of resources rapid industrialization unemployment income inadequacies as well as inefficient or non-existing waste management strategies This study examines the contributions of poverty as a reflection of income inadequacies and disparity to the availability of waste disposal facilities and its role in environmental degradation in Calabar urban area The research objectives are achieved though the identification of the disparity in household income distribution An assessment of the quality and quantity of waste disposal facilities available to housing units is made using primary and secondary data The findings reveal a wide pattern of disparity in household income and waste disposal facilities It is observed that the high density residential areas of Calabar South Local Government are not well served in waste management facilities resulting in environment degradation The medium and low density residential areas within the municipality are better served resulting in proper waste management The opinion of residents within the urban area is that government should be solely responsible for waste management